The Influence of Production Factors on the Productivity of Weather Modification Technology Services at the Center for Weather Modification Technology - Zaldy Lijuardy Salim (Journal of Entrepreneur and Business, 2024)
This study aims to determine the effect of flight costs, seedlings and production factors on TMC productivity, as well as the effect of production factors simultaneously on TMC productivity, as well as the effect of TMC productivity on TMC benefits. The object of this research is the Central Bureau of Weather Modification Technology customers. Center for Weather Modification Technology with its address at Gedung Geostech 820, Kawasan Puspitek, Setu, South Tangeran. Analysis tools using SPSS. The results of the study are the cost of flights and seedling costs not significantly positive effect on TMC productivity, HR costs have no significant negative effect on TMC productivity, also the three independent variables simultaneously have a significant positive effect on TMC productivity, but TMC productivity is found to be significantly positive effect on benefits TMC. Keywords : Production, Flight Costs, Seedling Costs, HR Costs, TMC Productivity